2012
DOI: 10.1002/jccs.201100322
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metallic and Organometallic Ions Scavenging Using Silica‐Based Adsorbent Functionalized with Ligands Containing Sulfur and Nitrogen Elements

Abstract: A variety of silica-based solid phases, whose surfaces are functionalized with ligands containing sulfur and nitrogen elements, are used as self-supporting adsorbents for environmental remediation evaluation and potential separation application. Each adsorbent is tested for its ability to scavenge five metallic ions: Hg 2+ , Cu 2+ , Cd 2+ , Mn 2+ , Pb 2+ , and two organometallic ions: ethylmercury and phenylmercury, from independent homoionic solutions at both neutral and acidic pH values. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Considering the nature of the analyte, the time required to reach the maximum percentage of adsorption decreased as the amount of adsorbent increased. The longer the elapsed time, the higher the percentage of analyte adsorbed as shown in Figure , all of which indicate that the adsorption process, in the case of both pesticidal compounds and biogenic amines, was surface-oriented and similar to that in a previous study . Except for the number of accessible interaction sites on the adsorbent, the viscosity of the liquid phase and the types of interactions between analyte and adsorbent are believed to affect the time required to reach the maximum percentage of adsorption.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Considering the nature of the analyte, the time required to reach the maximum percentage of adsorption decreased as the amount of adsorbent increased. The longer the elapsed time, the higher the percentage of analyte adsorbed as shown in Figure , all of which indicate that the adsorption process, in the case of both pesticidal compounds and biogenic amines, was surface-oriented and similar to that in a previous study . Except for the number of accessible interaction sites on the adsorbent, the viscosity of the liquid phase and the types of interactions between analyte and adsorbent are believed to affect the time required to reach the maximum percentage of adsorption.…”
Section: Resultssupporting
confidence: 69%
“…the case of both pesticidal compounds and biogenic amines, was surface-oriented and similar to that in a previous study. 28 Except for the number of accessible interaction sites on the adsorbent, the viscosity of the liquid phase and the types of interactions between analyte and adsorbent are believed to affect the time required to reach the maximum percentage of adsorption.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Regarding the variations among other elemental compositions between humic fractions collected under acidic and basic conditions, the possible explanation has been provided elsewhere. 37,41 The percentage of oxygen for the humic fractions collected under acidic conditions was always higher (Table 2), compared to those obtained under basic conditions. Previous studies have indicated that the oxygen elements in HA exist mainly in the form of carboxyl groups determined according to the IR signal intensity.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…In addition, the procedure for its chemical immobilization was efficient and reliable, which was essential for the adsorption evaluation with such a small amount of adsorbent (i.e., 10 mg) in the study. Regarding the variations among other elemental compositions between humic fractions collected under acidic and basic conditions, the possible explanation has been provided elsewhere. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…The results indicated that the time required to reach the maximum adsorption percentage may shorten as more adsorbent is used in the process (not shown). Furthermore, the low viscosity of hexane, a highly specific interaction resulting from the two functional carboxylate groups of analyte, and a significant interaction enhancement in hexane all contributed to the surface-oriented rapid adsorption, which was 80% complete in less than 40 min. ,, None of these results was reproducible or observable when using other organic solvents, such as ether, or when performed in an aqueous environment.…”
Section: Resultsmentioning
confidence: 99%